2018
DOI: 10.1007/s13632-018-0438-1
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Friction Stir Welding of Steel

Abstract: Defects associated with friction stir welding of two steel grades including DH36 and EH46 were investigated. Different welding parameters including tool rotational and tool traverse (linear) speeds were applied to understand their effect on weld seam defects including microcracks and voids formation. SEM images and infinite focus microscopy were employed to identify the defects types. Two new defects associated with the friction stir welding process are introduced in this work. The first defect identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…However, rather than to characterise the effectiveness of the NDT method, the scope of this work is to develop a computational framework that utilises the NDT method's data within a machine learning framework to enhance flaw detection. As such, we use representative FSW flaw sizes, without the intention of being exhaustive or as close to reality as possible (this would not be possible without utilising actual FSW flaws, mainly due to their irregular shapes [8], [36]). Note that a 0.6 mm thick layer was machined off the FS weld surface before machining the FBHs, to level out the weld's uneven surface.…”
Section: A Experimental Setup and Proceduresmentioning
confidence: 99%
“…However, rather than to characterise the effectiveness of the NDT method, the scope of this work is to develop a computational framework that utilises the NDT method's data within a machine learning framework to enhance flaw detection. As such, we use representative FSW flaw sizes, without the intention of being exhaustive or as close to reality as possible (this would not be possible without utilising actual FSW flaws, mainly due to their irregular shapes [8], [36]). Note that a 0.6 mm thick layer was machined off the FS weld surface before machining the FBHs, to level out the weld's uneven surface.…”
Section: A Experimental Setup and Proceduresmentioning
confidence: 99%
“…Zhang et al [33] observed that increasing the rotational speed to more than 1400 rpm caused the formation of voids in the SZ. Kim et al [34], Ren et al [35], and Moussawi et al [36] studied the influence of rotational and traverse speeds on defects formation during FSP of aluminum alloys. In this regard, investigating the thermal aspects (peak temperature and thermal distribution) of FSP has attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the near-surface stress concentration and the friction stir welded joint defect such as voids in the bottom of the welded joint, kissing bonds cracks, root sticking, weld root flaw, etc. will shorten the fatigue life [9]. Therefore, deep-rolling and post-weld heat treatment processes are used to improve FSW workpieces, making them stronger and giving them a longer fatigue life.…”
Section: Introductionmentioning
confidence: 99%